Low Carbohydrate Dietary Approaches for People With Type 2 Diabetes—A Narrative Review - Wheatley, Sean D.; Deakin, Trudi A.; Arjomandkhah, Nicola C.; Hollinrake, Paul B.; Reeves, Trudi E. (Frontiers in Nutrition, 2021)
Although carbohydrate restriction is not a new approach for the management of Type 2 diabetes, interest in its safety and efficacy has increased significantly in recent years. The purpose of the current narrative review is to summarise the key relevant research and practical considerations in this area, as well as to explore some of the common concerns expressed in relation to the use of such approaches. There is a strong physiological rationale supporting the role of carbohydrate restriction for the management of Type 2 diabetes, and available evidence suggests that low carbohydrate dietary approaches (LCDs) are as effective as, or superior to, other dietary approaches for its management. Importantly, LCDs appear to be more effective than other dietary approaches for facilitating a reduction in the requirement for certain medications, which leads to their effects on other health markers being underestimated. LCDs have also been demonstrated to be an effective method for achieving remission of Type 2 diabetes for some people. The available evidence does not support concerns that LCDs increase the risk of cardiovascular disease, that such approaches increase the risk of nutrient deficiencies, or that they are more difficult to adhere to than other dietary approaches. A growing number of organisations support the use of LCDs as a suitable choice for individuals with Type 2 diabetes.